Propagation measurements and prediction for indoor wlan application - Aboharba, Ibrahim M. Abdalla (2006)
The application of wireless local area network (WLAN) is increasing in offices, it become important to study signal propagation indoor environment. In this project, the Site Ware Technologies` site specific propagation prediction tool is a three-dimensional (3-D) ray tracing code employing modified shoot and bounce ray(SBR) method know as the Vertical Plane Launch (VPL) will be used to predict indoor propagation effects in Wireless Communication Center (WCC), Faculty of Electrical Engineering, University Technology Malaysia (UTM). Propagation prediction will be done within first floor of WCC at carrier frequency 2.4 GHz based on IEEE 802.11 b/g standard while measurement of signal strength will use Airmagent software for measure above mention area. after that presented simulation result into three dimensional using Matlab software .